Manajemen Anestesi pada Seksio Sesarea pada Pasien COVID-19 Derajat Berat - Uyun, Yusmein; Apsari, Ratih Kumala Fajar; Suharso, Pamungkas Hary (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
COVID-19 infection in pregnant patients can lead to premature labor. The most common method of delivery is by caesarean section. Many aspects must be considered in carrying out anesthesia for COVID-19 patients, including physiological changes that occur due to pregnancy and the effects of COVID-19 infection which can aggravate the condition of pregnant patients. Maintaining adequate oxygenation in the blood, choosing the right anesthetic agent, considering its effect on the fetus, and mechanical ventilation management related to ARDS caused by COVID-19 infection are several things that should be concerned in anesthesia management.